The Impact of the Principal's Leadership Style and Work Environment on Learning Effectiveness - Desiriani, Desiriani; Wisetsri, Worakamol; Utama, Hendri Budi (PPSDP International Journal of Education, 2022)
This study aims to determine the principal's leadership style and work climate and its relationship with learning effectiveness at SMK N 1 Lais, Lais District, Musi Banyuasin Regency. Design This study uses a quantitative method with an associative approach. The population in this study consisted of 42 teachers and 412 students. For the teacher sample, the entire population is taken so that it is called the research population. The research sample of students was taken by 15% of the 412 students, totaling 62 students. The data analysis technique used to test the hypothesis is simple and multiple linear regression analysis, t test and F test. In this study, the effectiveness of learning is the main target in improving the quality of education in general. In previous studies, more studied teacher performance factors as the focus of success. Therefore, increasing the effectiveness of learning needs serious attention from various parties, especially to improve factors related to learning effectiveness such as principals' leadership and work climate.